2022
DOI: 10.3390/w14172711
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the TiO2-Ag Photocatalytic Efficiency by Acetone in the Dye Removal from Wastewater

Abstract: TiO2 nanoparticles synthesized by the sol-gel method and doped with Ag were characterized by SEM, EDAX, FTIR, BET, XRD and TEM, then tested in the photocatalytic degradation of methylene blue (MB) under UV irradiation. The experimental results indicate that the average size of the raw particles was 10 nm, and their size was increased by calcination. The photocatalytic degradation of MB on nanostructured TiO2-Ag shows a high degradation efficiency upon the addition of a photosensitizer. A parametric study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…UV analyses performed on the catalyst showed that doping TiO 2 with silver allows to decrease the band gap energy of the semiconductor from 3.3 eV to 2.98 eV, thus increasing the photocatalytic activity of the material (Figures S2 and S3, Table S3). This phenomenon is also in accordance with the literature [28–32] . Indeed, Ag and TiO 2 form a Schottky barrier, that reduces the recombination rate of the e − /h + pairs, silver acting as an electron trap, [28,30,32] thanks to its lower Fermi level of 1.1 eV (Scheme 2).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…UV analyses performed on the catalyst showed that doping TiO 2 with silver allows to decrease the band gap energy of the semiconductor from 3.3 eV to 2.98 eV, thus increasing the photocatalytic activity of the material (Figures S2 and S3, Table S3). This phenomenon is also in accordance with the literature [28–32] . Indeed, Ag and TiO 2 form a Schottky barrier, that reduces the recombination rate of the e − /h + pairs, silver acting as an electron trap, [28,30,32] thanks to its lower Fermi level of 1.1 eV (Scheme 2).…”
Section: Resultssupporting
confidence: 90%
“…After the reaction, the reactor was opened to air and the solution was filtered through a 0.20 μm syringe filter to remove the catalyst. The solution was then analysed by GC for quantification (details in the supporting information), and/or by 31 P NMR (spectra acquired on 400 MHz Bruker instruments at the Ecole Nationale Supérieure de Chimie de Rennes).…”
Section: Photocatalytic Experimentsmentioning
confidence: 99%
“…Qutub et al reported the use of CdS in improving the photocatalytic efficiency of TiO 2 in the visible region . Duduman et al used Ag-doped TiO 2 for dye degradation, and they found that the incorporation of Ag effectively improved the photocatalytic activity of TiO 2 by controlling the carrier charge recombination . Pandiyan et al reported the synthesis of the Ag–Sn bimetallic nanocomposite for the dye degradation in the visible region .…”
Section: Introductionmentioning
confidence: 99%
“…14 Duduman et al used Ag-doped TiO 2 for dye degradation, and they found that the incorporation of Ag effectively improved the photocatalytic activity of TiO 2 by controlling the carrier charge recombination. 15 Pandiyan et al reported the synthesis of the Ag−Sn bimetallic nanocomposite for the dye degradation in the visible region. 16 Hossein et al synthesized the graphene dot-grafted TiO 2 composite, which enhanced the photocatalytic efficiency by 85% under UV light illumination, because the graphene dot not only improved the charge transfer but also enhanced the absorption of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is also in accordance with the literature. [28][29][30][31][32] Indeed, Ag and TiO 2 form a Schottky barrier, that reduces the recombination rate of the e -/h + pairs, silver acting as an electron trap. [28,30,32] According to several works, the silver species are composed of metal Ag 0 , which is known to stabilize the photocatalyst [33] and Ag + species, that come from partial oxidation of the photodeposited metal in air.…”
mentioning
confidence: 99%